2021
DOI: 10.1002/anie.202108698
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Responsive Material Based on Catechol‐Modified Self‐Immolative Poly(Disulfide) Backbones

Abstract: Functional materials engineered to degrade upon triggering are in high demand due their potentially lower impact on the environment as well as their use in sensing and in medical applications. Here, stimuli‐responsive polymers are prepared by decorating a self‐immolative poly(dithiothreitol) backbone with pendant catechol units. The highly functional polymer is fashioned into stimuli‐responsive gels, formed through pH‐dependent catecholato–metal ion cross‐links. The gels degrade in response to specific environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
(79 reference statements)
0
32
0
Order By: Relevance
“…The former can be realized by modulating the ring strain of 1,2-dithiolanes using a substituent effect, such as the Thorpe–Ingold effect. Some recent studies on synthesis and modification methodologies expanded the building block library of 1,2-dithiolanes. Six-membered disulfide rings are also polymerizable, , despite the fact that their lower ring strain contributes a lower enthalpic force for the ROP when compared to five-membered 1,2-dithiolanes. The diselenium bond is an emerging type of dynamic covalent bond. Replacing the two sulfur atoms with selenium atoms can produce diselenium-mediated materials with unique dynamic properties.…”
Section: Trends In Applicationsmentioning
confidence: 99%
“…The former can be realized by modulating the ring strain of 1,2-dithiolanes using a substituent effect, such as the Thorpe–Ingold effect. Some recent studies on synthesis and modification methodologies expanded the building block library of 1,2-dithiolanes. Six-membered disulfide rings are also polymerizable, , despite the fact that their lower ring strain contributes a lower enthalpic force for the ROP when compared to five-membered 1,2-dithiolanes. The diselenium bond is an emerging type of dynamic covalent bond. Replacing the two sulfur atoms with selenium atoms can produce diselenium-mediated materials with unique dynamic properties.…”
Section: Trends In Applicationsmentioning
confidence: 99%
“…The gel degradation, resulting from sequential disassembly of the polymer backbone was visualized by the release of an encapsulated dye. 57,58 ■ MISCELLANEOUS EXAMPLES OF POLYMERS…”
Section: ■ Polymers With Sequential Disassembly Mechanism Initiated F...mentioning
confidence: 99%
“…In subsequent work, Daasbjerg and co-workers showed that, by decorating the self-immolative poly­(DTT) backbone with pendant catechol units, the polymer could be shaped into stimuli-responsive gels, generated through pH-dependent catecholato–metal ion cross-links. The gel degradation, resulting from sequential disassembly of the polymer backbone was visualized by the release of an encapsulated dye. , …”
Section: Polymers With Sequential Disassembly Mechanism Initiated Fro...mentioning
confidence: 99%
“…The ring-opening polymerization (ROP) of 1,2-dithiolanes affords polydisulfides (PDS) with fascinating self-adaptive, highly dynamic, and stimuli-responsive properties. Lipoic acid (LPA) and its derivatives, for example, are the most frequently studied 1,2-dithiolane monomers for their biogenesis source, intrinsic biocompatibility, and ease of modification. Although the polymerization of LPA can be traced back to as early as the 1940s, the PDS were not explicitly explored until the past decade. , A series of pioneering works were accomplished by Matile and co-workers, who reported LPA-derived PDS with unusual thiol–disulfide exchange-mediated cellular penetration ability. Yao et al have coupled various LPA-derived PDS to nanoparticles and proteins, achieving efficient cytosolic delivery of the cargos. Waymouth and Moore et al have carefully studied the polymerizability of various 1,2-dithiolanes and the topology control of PDS in organic solvents, respectively. , Moreover, Qu and Feringa et al have together fabricated various fascinating self-healing and recyclable bulk PDS-based materials. Taking advantage of their unique properties of PDS, numerous new applications have been demonstrated including hydrogels, catalysis, gene delivery, etc. , …”
Section: Introductionmentioning
confidence: 99%